Cross Cultural Adaptation: Kuesioner Strategi Motivasi Belajar (Mslq) Subsskala Efikasi Diri dalam Belajar dan Mengerjakan Tugas Versi Indonesia - Arief Budiman; Elsye Maria Rosa; Moh Afandi (Jurnal Ilmu Kesehatan, 2017)
Background: Self-efficacy is an important factor for establishing of learning independence, self efficacy gives influence to motivation, perseverance to overcome difficulties and learning achievement. Therefore a measuring instrument is needed to assess valid and reliable self efficacy. In this study cross cultural adaptation in Indonesian version from MSLQ subscale self-efficacy for learning and performance is used to to measure self efficacy of nursing students.Method: This study used a five- steps cross cultural adaptation that are translation, synthesis, back translation and final questionnaire in Indonesian version is assesed content validity index (CVI) with consideration of three experts, than is tested to assess for validity and reliability to eighty-eight the nursing academy diploma students YARSI in Samarinda city.Result: Through the stage of cross cultural adaptation there is have addition of the number of questionnaire items from 8 to 27 statement items and based on the value of CVI using the formula Aiken`s V is obtained coefficient value of all item statement > 0.5 , the test results of the questionnaire validity of all item have significance value > 0.05 and the questionnaire reliability of all item have alpha cronbach value > 0.6Conclusion: The MSLQ subscale self-efficacy for learning and performance instrument in Indonesia version has Content Validity Index (CVI) where is eligible with overall item are valid and reliable, so the instrument can be used in the target population of nursing students.